2016
DOI: 10.1159/000447605
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous Malformations in the Pediatric Population: Review of the Existing Literature

Abstract: Arteriovenous malformations (AVMs) in the pediatric population are relatively rare but reportedly carry a higher rate of rupture than in adults. This could be due to the fact that most pediatric AVMs are only detected after rupture. We aimed to review the current literature regarding the natural history and the clinical outcome after multimodality AVM treatment in the pediatric population, as optimal management for pediatric AVMs remains controversial. A multidisciplinary approach using multimodality therapy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 55 publications
(83 reference statements)
0
60
0
1
Order By: Relevance
“…In the survey, younger age was not considered a reason to withhold treatment by all the participants and surgery was suggested by 85% of the panel [9,28,32].…”
Section: And Is Eloquence a Contraindication To Treatment?mentioning
confidence: 99%
“…In the survey, younger age was not considered a reason to withhold treatment by all the participants and surgery was suggested by 85% of the panel [9,28,32].…”
Section: And Is Eloquence a Contraindication To Treatment?mentioning
confidence: 99%
“…23 If the AVM is only partially obliterated with radiosurgery, studies have suggested that the rupture risk may be similar to the natural history of 2.6% per year. 8 Additionally, in ARUBA (A Randomized Trial of Unruptured Brain Arteriovenous Malformations), which compared the risk of death and symptomatic stroke in adult patients with unruptured cerebral AVMs randomly assigned to medical management or medical management plus intervention, including neurosurgical, endovascular, or radiotherapy procedures, researchers found a significantly lower risk of death and neurological disability at 30 months' follow-up in the medical management group (15.1% vs 46.2%). 19 While the ARUBA findings are not generalizable to pediatric populations, based on an extrapolation of its findings and for the reasons aforementioned, we propose serial surveillance as a viable option in patients with high-grade unresectable lesions.…”
Section: The Role Of Srsmentioning
confidence: 99%
“…Arteriovenous Malformations (AVMs) refers to anomalous proliferation or collection of dilated arteries and veins within the brain parenchyma with an anomalous superseding capillary bed, instigating shunting [1] [2] [3]. The occurrences of cerebral AVMs are uncommon in pediatric age group, although they are believed to be congenital [3] [4].…”
Section: Introductionmentioning
confidence: 99%
“…The occurrences of cerebral AVMs are uncommon in pediatric age group, although they are believed to be congenital [3] [4]. In children, AVMs can manifest as spontaneous hemorrhage resulting in hydrocephalus, non-specific headaches, epilepsy or focal neurological deficit [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation